Analysis Job Satisfaction with Leader Member Exchange and Organizational Climate Through Organization Citizenship Behavior in Company: Analisis Kepuasan Kerja dengan Leader Member Exchange dan Iklim Organisasi Melalui Organization Citizenship Behavior pada Perusahaan - Muarofah, Siti; Abadiyah, Rifda (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine and analyze the influence of leader member exchange and organizational climate through organization citizenship behavior on job satisfaction of PT. Pabrik Gula Candi Baru.The research uses a quantitative approach. The sample in this study is the entire staff of PT. Candi Baru Sugar Factory with 34 employees. The analysis technique in this study uses path analysis, with t test and F test as research hypothesis testing. The results showed that: 1) Leader member exchange proved to have a significant effect on job satisfaction, 2) Organizational climate proved to have a significant effect on job satisfaction, 3) Leader member exchange proved to have a significant effect on job satisfaction through organizational citizenship behavior, 4) Organizational climate proved to have an effect. significant effect on job satisfaction through organization citizenship behavior, 5) Organization citizenship behavior has been proven to have a significant effect on job satisfaction for employees of PT. Pabrik Gula Candi Baru.